ANALYSIS OF HONEYCOMB SANDWICH PANEL FOR APPLICATION OF DOOR MATERIAL FOR LIGHT WEIGHT VEHICLE - Mr.Lande Pradip R; Mr. Kharad Bharat N (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Car door is one of the main parts which are used as protection for passengers from side collisions. Presently steel is used for car doors construction. The aim of the project is to analyze the car door with presently used material steel and replacing with composite materials like Honey Comb Structure. Weight reduction is now the main issue in automobile industries. Traditionally most common material for manufacturing vehicle Door is mild steel, in various forms. Over time, other materials have come into use, the majority of which have been is steel and Aluminum. In this project traditional materials are replaced with compositematerials. Using reverse engineering method.(Existing model, modified model, honey comb model).Impact analysis is conducted on door for different speeds by varying the materials. Best of the result we will consider for the door design. Also we are going to reduce weight of the door by using composite materials. By this we have to reduce the damage percentage of the car and passenger protection. In this project, the Car door is modeled using parametric modeling software Pro/Engineer. Pro/ENGINEER is the standard in 3D product design, featuring industry-leading productivity tools that promote best practices in design. We have to variety the materials of the car door and speed to impacting of door